Health seeking behaviour of geriatric population in rural area of Puducherry: a community based cross sectional study - Gnanasabai, Gnanamani; Kumar, Mohan; Boovaragasamy, Chithra; Rahman, Mujibur; Ramamurthy, Poovitha (International Journal Of Community Medicine And Public Health, 2020)
Background: Population ageing is a great concern for the health sector. The health-seeking behaviour of elderly individuals can help in ascertaining their needs and priorities to develop appropriate policies for their care and avert disease progression. Objective was to assess health seeking behaviour of the elderly residing in rural Puducherry. Methods: A community based cross-sectional descriptive study was conducted among the geriatric population residing in selected areas of rural Puducherry. Interviews using semi-structured pretested proforma were conducted for capturing information on health seeking behaviour. Results: Out of the total study participants, 403 (64.8%) were suffering from chronic illness. Around 81.1% of them were seeking treatment. Majority of the elders (97.9%) preferred Allopathy system for their chronic illness. Conclusions: Awareness among the elderly population is imperative and can be done by regular medical check-ups by ensuring early detection of the chronic diseases and curtail complications.